2m+4n+6m+5n=

Simple and best practice solution for 2m+4n+6m+5n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+4n+6m+5n= equation:


Simplifying
2m + 4n + 6m + 5n = 0

Reorder the terms:
2m + 6m + 4n + 5n = 0

Combine like terms: 2m + 6m = 8m
8m + 4n + 5n = 0

Combine like terms: 4n + 5n = 9n
8m + 9n = 0

Solving
8m + 9n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9n' to each side of the equation.
8m + 9n + -9n = 0 + -9n

Combine like terms: 9n + -9n = 0
8m + 0 = 0 + -9n
8m = 0 + -9n
Remove the zero:
8m = -9n

Divide each side by '8'.
m = -1.125n

Simplifying
m = -1.125n

See similar equations:

| 6.9=9.6 | | y^4-1= | | -6(3p+4)=16+2p | | 3+2(1-3x)=1-2x | | x^10-16= | | 4v=5(v+1) | | X-6=-13/2 | | x^5-80x= | | 1.4x=43.90 | | 7(x+6)=6(x-7)+x | | -83p+7p-5p+5+30= | | -2(3x-2)=4x-16 | | n/9+1=12 | | (4/5)c-8=-36 | | 12x^3+40x^2-32x= | | 2r+5s-18+6r= | | -2=(k/4)-7 | | 3(-6k+3)+2k=-29+3k | | 7[7-(-3x-4)]=126x+217 | | r^3-12r^2-144r+1728= | | 5k+3k-7p= | | n-(3/5)=-(5/6) | | n-4(3n-3)=-4n+5 | | (9y+8)(7y+26)=0 | | a^3+10a^2+25a= | | (9y+8)(8y+26)=0 | | 3m+2m+4n= | | -31+6x=2x+27 | | (3/4)p=18 | | 6(1+103x)=9 | | -16-2x=8-6x | | 2+3a=2(1-a) |

Equations solver categories